PEMIKIRAN PESTALOZZI TENTANG PENDIDIKAN - Sadiran Sadiran (Institut Agama Islam Ngawi, 2022)
Abstract: the basic principles of teaching that Pestalozzi advocated can be seen in the methods of teaching subjects in modern schools, such as arithmetic, language, geography, drawing, composing, natural education, physical education, manual work and music. Although his teaching methods in the classroom were sometimes inconsistent and impractical, his methods and approaches were widely used in the late 19th and early 20th centuries. Pestalozzi's teaching method is based on a general conclusion that knowledge must start from an understanding, observation and relationship with nature, all of which are experiences instead of words or books. Students should be guided by an attentive teacher, one who really understands about children and the lessons to be taught. Each student also needs careful guidance in choosing objects or natural phenomena that they will observe and what kind of relationship they must live by formulating certain principles in the lesson. Pestalozzi's thinking in educational programs emphasizes understanding, natural science education, arithmetic by rote and the teaching of music, drawing and handwriting. Keywords: Petalozzi Thought and Education